Analisis Kelayakan Finansial Pada Proyek Renovasi Bangunan Gedung Dengan Fungsi Usaha Hunian - Septian, Ridho; Astuti , Santi Widi; Mariam, Evi Siti; Rizki, Meliana; Prawira, Yuda; Airlangga, Dito Adam (Jurnal Rekayasa Infrastruktur, 2025)
The Population and Civil Registration Service DKI Jakarta, noted that the number of immigrants increases almost every year. Therefore, the need for temporary housing also increases. On this basis, investment in residential business buildings is a promising business. South Jakarta in particular is currently one of the most popular destinations for immigrants. This strategic location is what makes investors interested in investing their money in the form of property businesses such as residential business buildings. This paper aims to analyze the financial feasibility of the residential business building project. The financial feasibility analysis of residential business buildings is carried out using the Net Present Value (NPV) and Internal Rate of Return (IRR) methods. Sensitivity analysis is carried out to determine a variable that affects this residential business building business. From the NPV calculation, a value of Rp. 655,115,548 is obtained, financially feasible (NPV> 0). The IRR percentage value obtained is 8.42% with a MARR of 7.90% (IRR> MARR), so this renovation project is financially feasible. Sensitivity analysis shows that the project is not feasible at bank repayment interest rates greater than 8.49%, occupancy less than 26 rooms and construction cost increases greater than 11.87%.